CO detection of hydrothermally synthesized Pt-loaded WO3films - Samerjai,T. (American Scientific Publishers, 2015)
Copyright © 2014 American Scientific Publishers All rights reserved. Unloaded WO3and 0.25-1.0 wt% Pt-loaded WO3nanoparticles were synthesized by hydrothermal method using sodium tungstate dihydrate and sodium chloride as precursors in the acidic condition and further by the impregnation method using platinum acetylacetonate. Pt-loaded WO3films on Al2O3substrate interdigitated with Au electrodes were prepared by spin-coating technique. The temperature has an obvious influence on the response of sensors to CO gas. In order to determine the optimal operating temperatures, the response of WO3sensors with different Pt loading concentrations towards 50-2000 ppm of CO in air was tested as a function of operating temperature of 150-350°C. It was found that 1.0 wt% Pt-loaded WO3sensing film showed the highest response of ∼ 469 at 2000 ppm CO (250°C). Therefore an optimal operating temperature of 250°C was chosen for CO detection.